Persepsi Jamaah terhadap Pengajian Mingguan di Majelis Taklim Nurul Abror Karawang - Rafly, Muhammad; Suherdiana, Dadan; Nase, Nase (Tabligh: Jurnal Komunikasi dan Penyiaran Islam, 2023)
The aim of this research is to determine the congregation's perception of weekly recitation activities at the Nurul Abror Taklim Assembly through three focuses research includes receiving stimuli, understanding, and assessing. The theory used is the perception theory mentioned by Bimo Walgito. This research uses a qualitative approach with descriptive methods. It can be concluded that the perception generated by the congregation regarding the weekly recitation activities shows that the bil-lisan da'wah method is used in the process of receiving stimulation from the congregation in these activities. The congregation applies Islamic values in their daily lives from the material presented as a form of understanding of the activity. The positive impression that arises from the assessment is that the congregation becomes reflective.